Is long-term PM1 exposure associated with blood lipids and dyslipidemias in a Chinese rural population?. (May 2020) - Mao, Shuyuan; Li, Shanshan; Wang, Chongjian; Liu, Yisi; Li, Na; Liu, Feifei; Huang, Shuqiong; Liu, Suyang; Lu, Yuanan; Mao, Zhenxing; Huo, Wenqian; Chen, Gongbo; et al.
Highlights: Rural residents in central China were exposed to high levels of PM1 . PM1 exposure was related to increased TC and LDL-C, and decreased TG and HDL-C. High levels of PM1 was associated with higher risk of dyslipidemias. Males, older and overweight participants were vulnerable to adverse effects of PM1 . Abstract: Background: Air pollution has been shown to be associated with blood lipid levels. However, studies on long-term ambient particulate matter with aerodynamic diameter ≤1 μm (PM1 ) exposure in high-exposure areas are still limited. This study aimed to explore the associations among long-term PM1 exposure, blood lipids and dyslipidemias. Methods: Baseline data of The Henan Rural Cohort study was used in present study, including a total of 39, 259 participants aged from 18 to 79 years. Daily levels of PM1 were estimated by a spatiotemporal model using ground-level measurements of PM1, satellite remote sensing data and other predictors, according to participants' home addresses. Individual exposure to PM1 was the 3-year average before baseline investigation. Linear regression and logistic regression models were applied to examine the associations among PM1, blood lipids ((total cholesterol (TC), triglyceride (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C)), and prevalence of dyslipidemias. Results: The 3-year concentration of PM1 was 55.7 ± 2.1 μg/m 3 . Each 1 μg/m 3 increment of PM1 was associated with an increase of 0.21% (95% confidence interval (CI): 0.11%–0.31%) in TC and 0.75% (95% CI: 0.61%–0.90%) in LDL-C, while decrease of 2.68% (95% CI: 2.43%–2.93%) in TG and 0.47% (95% CI: 0.35%–0.59%) in HDL-C. Each 1 μg/m 3 increase in PM1 was associated with 6% (95% CI: 4%–8%), 3% (95% CI: 2%–5%) and 5% (95% CI: 3%–7%) higher risks of hypercholesterolemia, hyperbetalipoproteinemia and hypoalphalipoproteinemia. Sex, age and BMI statistically modified the associations between PM1 with blood lipid levels and dyslipidemias. Conclusions: Higher PM1 exposure was associated with adverse changes of blood lipid levels and dyslipidemias. Males, older and overweight participants were susceptive to the adverse effects of PM1 .